Improving performance of mobile ad hoc networks using efficient Tactical On Demand Distance Vector (TAODV) routing algorithm - Uddin, Mueen; Abdul Rahman, Azizah; Alarifi, Abdulrahman; Talha, Muhammad; Shah, Asadullah; Iftikhar, Mohsin; Zomaya, Albert (ICIC International, 2012)
Ad hoc network is a group of wireless mobile computers (or nodes), in which individual nodes cooperate by forwarding packets for each other to allow nodes to commu- nicate beyond direct wireless transmission range. Previous research in ad hoc networking has generally studied the routing problem in a non-adversarial setting by assuming a trusted environment. In this paper, we present the design and performance evaluation of a new efficient on demand routing protocol for mobile ad-hoc networks. Up till now many routing algorithms have been proposed to solve the routing problem in mobile ad- hoc networks so it is difficult to compare the performance of different routing protocols qualitatively as there are many parameters that affect the performance of network. This paper presents that the proposed on demand routing algorithm performs better in mobile ad-hoc environment than other traditional algorithms. The proposed TAODV algorithm performs better for solving routing problems in Mobile Ad Hoc networks. It also describes the design of a novel on-demand routing algorithm. Most of the proposed algorithms use a blind ooding technique during the route discovery process. This method is inefficient and creates excessive routing overhead. To overcome this problem, the proposed routing protocol uses a query localization technique that signicantly reduces the network traffic and increases the performance of network. The simulation results clearly show that pro- posed on demand routing protocol is more efficient and scalable than existing ones. Keywords: Ad hoc on demand distance vector routing, Mobile ad hoc network, Po- sitional communication systems, Query localization technique, Tactical on demand dis- tance vector (TAODV) and wireless networks